Persepsi Pelaku UMKM Terhadap Kepemilikan Sertifikasi Halal Untuk Meningkatkan Daya Saing Produk UMKM Madura - Nor Qomariyah (ITB AAS INDONESIA Surakarta, 2023)
Halal certification will increase the competitiveness of micro small business (UMKM ) products, especially food and beverages, moreover there is a policy from related agencies that all food and beverage products must be halal certified. This study aims to determine the perceptions of halal certification in micro small business actors in the food and beverage sector in Bangkalan and Pamekasan Regencies and what are the factors that influence perceptions of these micro small business actors. The analytical method used in this study is a quantitative descriptive method using a Likert scale. The results of the study show that the average perceived value of UMKM actors ranges from 3.81 to 4.75, which is in the good category. While the factors that influence the perception of UMKM actors are awareness of the importance of halal certification by 55 percent, an increase in product quality which will affect price increases, the desire to increase the competitiveness of their products by 74 percent, the availability of adequate input sources by 51 percent of respondents. willing to provide halal input sources, and have consumers who are aware of the importance of halal products as much as 89 percent considering that the people of Bangkalan and Pameksan are predominantly Muslim.